MEDIASI PENAL SEBAGAI UPAYA ALTERNATIF PENANGANAN KEKERASAN DALAM RUMAH TANGGA - Laely Wulandari; Ainul Azizah (Masalah-Masalah Hukum, 2011)
The domestic Violence (KORT) represent hardness type owning the nature of typicallu done within doors, victim and perpetrator is family member and also oftentimes assumed by non as hardness form. Code Abolition ofKDRT give the basis for strong law which make KORT which initially housewifery become state business. But practically many KORT case which do not be continued to conference process because is assorted of factor. For example, feeling small, length process conference, not accomodate of importance of victim . This fact cause shall be thought of by a way of protecting everybody in household, giving to feel balmy/y, without lessening action able to be taken to KORT perpetrator. Rational Policy able to be acceptfid by all party needed in KORT handling. Require to be thought of by the way of which win-win solition for the case of KORT ini. Mediasi can be made one of choice, but mediasi in criminal law is unknown. For that this research will look for answers to problems; Is The Penal Mediation can can be used for handling of problem of KORT and How the regulation in future The Penal Mediation for Domestic violence. The conclusion are: The Penal mediation can use for the case of domestic violence, and the regulation formulation which will come which must be paid attention is common p1inciples from mediasi penal, Step mediasi penal, model which can be utilized, The mediator, types of violence can be mediation and duration of penal mediation. Given Suggestion are lt'on snot easy to integration penal mediation on the criminal justice system. First we must socialization about this to the public and penal mediation should not add burden to criminal justice system.